2013
DOI: 10.1074/jbc.m112.406009
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase, WWP1, Interacts with AMPKα2 and Down-regulates Its Expression in Skeletal Muscle C2C12 Cells

Abstract: Background:The role of the ubiquitin-proteasome pathway under high glucose conditions is unclear. Results: AMPK␣2 interacts with WWP1, and its expression is down-regulated by the ubiquitin proteasome pathway in high glucose culture conditions in C2C12 cells. Conclusion: WWP1 down-regulates AMPK␣2 expression through direct interaction in high glucose culture conditions of skeletal muscle C2C12 cells. Significance: The ubiquitin proteasome pathway may involve high glucose-induced AMPK␣2 down-regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Previous reports have shown that Gremlin-1 expression can also be stimulated by increasing glucose levels (Gremlin-1 was once termed increased-in-high-glucoseprotein-2) (58). This is consistent with the effect of glucose on Smurf-1 ( Figure 5) and other ubiquitin ligases (59), as well as with the role of hyperglycemia on Gremlin-1 in podocyte injury (60) and cell proliferation in mesangial cells (61). It is possible that Smurf-1 is regulated by glucose uptake/metabolism by mechanisms similar to those of Gremlin-1, in which transforming growth factor b-1 (TGFb-1) signaling pathways are amplified (60,62).…”
Section: Original Researchsupporting
confidence: 68%
“…Previous reports have shown that Gremlin-1 expression can also be stimulated by increasing glucose levels (Gremlin-1 was once termed increased-in-high-glucoseprotein-2) (58). This is consistent with the effect of glucose on Smurf-1 ( Figure 5) and other ubiquitin ligases (59), as well as with the role of hyperglycemia on Gremlin-1 in podocyte injury (60) and cell proliferation in mesangial cells (61). It is possible that Smurf-1 is regulated by glucose uptake/metabolism by mechanisms similar to those of Gremlin-1, in which transforming growth factor b-1 (TGFb-1) signaling pathways are amplified (60,62).…”
Section: Original Researchsupporting
confidence: 68%
“…AMPKα2 levels in mouse myoblast cells are similarly down-regulated in response to glucose by the Ubiquitin E3-ligase Wwp1 (62).…”
Section: Discussionmentioning
confidence: 85%
“…Under energy stress, USP10 removes the ubiquitination of AMPKα and expose AMPKα to LKB1. Recent studies have also shown that ubiquitination of AMPKα could mediate its degradation under certain conditions (Lee et al, 2013; Pineda et al, 2015). However, in our experimental systems, the ubiquitination of AMPKα does not affect its protein level.…”
Section: Discussionmentioning
confidence: 99%